Astroid!

Calculus Level 2

What is the length of the arc of the curve x 2 3 + y 2 3 = 4 x^{\frac{2}{3}} + y^{\frac{2}{3}}=4 ?

24 48 12 96

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Lokeshwar Tabjula
Aug 22, 2014

We use the parametric equations x = 8 cos 3 t x = 8\cos^3t and y = 8 sin 3 t y = 8\sin^3t to describe the given curve.

Now, we use the arclength formula for parametric equations: L = a b ( d x d t ) 2 + ( d y d t ) 2 d t L = \int_{a}^{b}\sqrt{\left(\frac{dx}{dt}\right)^2 + \left(\frac{dy}{dt}\right)^2}dt

We'll find the length of the curve that exists solely in the first quadrant and then multiply this by 4. 0 π 2 ( 24 cos 2 t sin t ) 2 + ( 24 sin 2 t cos t ) 2 d t \int_{0}^{\frac{\pi}{2}}\sqrt{\left(-24\cos^2t \sin{t} \right)^2 + \left(24\sin^2t \cos{t} \right)^2}dt 0 π 2 24 sin t cos t d t = 12 sin 2 t 0 π 2 = 12 \int_{0}^{\frac{\pi}{2}}24\sin{t}\cos{t}dt = 12\sin^2t \Big|_{0}^{\frac{\pi}{2}} = 12

Multiplying this by four gives an area of 48.

Multiply by 4 gives an arc length of 48

Jerry McKenzie - 8 months, 3 weeks ago

You don’t need to do any of this. If you retool the equation into the equation of a circle using some algebra voodoo, you can use s = r(theta) to find the exact arc length as 16pi.

x^(2/3) + y^(2/3) = 4

If you write 4 as 2^(2) and put both the left and right sides to the third power, you’ll see that cuberoot(2^6) = 4, so the equation’s arc length is equivalent to

x^2 + y^2 = 64.

The angle in radians is 2pi, so 8*2pi = 16pi ~ 50.26

Jesse Olsson - 4 months ago

how can you come up with the parametrization of x x and y y ?

Bostang Palaguna - 2 months, 3 weeks ago
Bostang Palaguna
Mar 20, 2021

Standard length of curve calculation (without using parametrization):

x 2 / 3 + y 2 / 3 = 4 y = ( 4 x 2 / 3 ) 3 / 2 x^{2/3} + y^{2/3} = 4 \leftrightarrow y = (4-x^{2/3})^{3/2}

so, y = 4 x 2 / 3 x 1 / 3 y' = -\sqrt{4-x^{2/3}}x^{-1/3}

notice that the graph would produce the same curve for 4 quadrants, so:

L = 4 × 0 8 1 + y 2 L = 4 \times \int_{0}^{8} \sqrt{1 + y'^2} = 4 × 0 8 1 + 4 x 2 / 3 x 2 / 3 = 4 \times \int_{0}^{8} \sqrt{1 + \frac{4-x^{2/3}}{x^{2/3}}} = 4 × 0 8 2 x 2 / 3 = 4 \times \int_{0}^{8} 2 \sqrt{x^{-2/3}} = 4 × 0 8 2 x 1 / 3 = 4 \times \int_{0}^{8} 2 x^{-1/3} = 48 = \boxed{48}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...